Synthesis and Sensing Properties of ZnO/ZnS Nanocages - Wang Hong-Li; Yu Xue-Lian; Ji Hui-Ming; Sun Jing; Du Xi-Wen (Nanoscale Research Letters, 2010)
Abstract Large-scale uniform ZnO dumbbells and ZnO/ZnS hollow nanocages were successfully synthesized via a facile hydrothermal route combined with subsequent etching treatment. The nanocages were formed through preferential dissolution of the twinned (0001) plane of ZnO dumbbells. Due to their special morphology, the hollow nanocages show better sensing properties to ethanol than ZnO dumbbells. The gain in sensitivity is attributed to both the interface between ZnO and ZnS heterostructure and their hollow architecture that promotes analyte diffusion and increases the available active surface area.